Rancang Bangun Pengering Ikan Asin Cerdas dengan Monitoring Internet of Things (IoT) - Isnaini Kurnia; Henna Nurdiansari; Elly Kusumawati (Pusat riset dan Inovasi Nasional, 2025)
Fish is one of the easiest foods to get, but fish easily spoil. So there are 2 methods to extend the life of fish so that they do not experience a spoilage, namely drying and salting. In the 4.0 era, technology is growing rapidly, one of which is IoT-based technology, in order to help all activities carried out by humans to be more effective and efficient. The purpose of this study is to design an automatic salted fish dryer system using the Internet of Things (IoT) and determine the performance effectiveness of salted fish dryers using the Internet of Things (IoT). The research method of this scientific paper uses an experimental method to test the hypothesis that will be proposed and is useful for predicting an event. Data collection techniques using literature study, data collection, needs analysis, application design and application programming as well as algorithm implementation. Based on the results of the research, the design of an automatic salted fish drying equipment system based on the Internet of Things (IoT) has the ability to monitor the movement of the tool through a smartphone. All components of the appliance can operate automatically just by pressing the start button and setting the duration of the time and the existence of an Internet of Things (IoT)-based salted fish drying device can facilitate and streamline the time when the process of drying fish into salted fish. Initially, small anchovies weighing 100 grams were dried for 3 days, but after using a salted fish dryer, the drying process was reduced to 3 hours (09.00 a.m-13.00 p.m) with a moisture content of 18 grams, while small flying fish weighing 100 grams required a drying process for 5 days (09.00 a.m-13.00 p.m) and would have a moisture content of 30 grams in 3 hours after using a salted fish dryer.